MAKNA SIRIH DALAM TARI MAKAN SIRIH DI TANJUNG BATU KECAMATAN KUNDUR KABUPATEN KARIMUN KEPULAUAN RIAU - Maidilla Siska Putri; Afifah Asriati; Indrayuda Indrayuda (SENDRATASIK UNP, 2014)
Abstract This article aimed at describing the function of “ sirih” in “ Makan Sirih” dance in Tanjung Batu, Kundur, Karimun, Riau. This dance is used by Riau civilians to welcome the guest. It is usally performed in official events. The data used in this research was descriptive qualitative analysis. The instrument of this research was the researcher accompanied by any tools, camera, and recorder. The technique of data collection used through literature study, interview and observation. The result showed that the performed of “Makan Sirih” dance in the guest was as social and cultural function. The social function of “sirih” is to describe the interaction between the civilians and the guest. The cultural function of “ sirih “ is as the custom of society to respect and appreciate the guests.   Kata Kunci : Tari Makan Sirih, Makna.